ANALISIS ALIRAN MASSA SAMPAH PADA SISTEM PERSAMPAHAN KOTA SURABAYA - Nieke Karnaningroem (Purifikasi, 2004)
To lengthen the life of solid waste final disposal site (TPA) the mass flow of solid should reduced by reduction, recycling and solid waste processings. The mass flow can be determined by surveys of the waste mass at source, at temporary disposal site (TPS) and TPA. The survey was done at markets, commercial, housing areas of high, medium and low income groups. Recycling rate of solid waste in Surabaya City was 16%, 13% at TPA and 3% at TPS. The solid waste generation was 5.655 ton/day and those which enter the was 3.118 ton/day. Solid waste that was deposited at TPA was 2.896 ton/day.